Method for producing starch nanofibers by electrospinning

Through the electrospinning method of treating high amylose solution with shear uniformity, the use of organic solvents is avoided, and the safety risks and time consumption in the production process are solved, and the efficient production of bead-free and uniform diameter starch nanofibers is achieved, which expands its application in food, drugs and cosmetics.

JP7628345B2Active Publication Date: 2025-02-10YANGZHOU UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2023537071
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-10-27
Filing Date
2022-08-15
Publication Date
2025-02-10
Estimated Expiration
2042-08-15

AI Technical Summary

Technical Problem

The prior art requires the use of a large amount of organic solvents when producing starch nanofibers, which leads to safety risks. The dry and wet electrospinning process takes a long time and the fiber diameter is large, which limits its application in the fields of food, medicine and cosmetics.

Method used

The high amylose solution is treated with shear homogenization, and the starch nanofibers are produced by electrospinning, avoiding the use of organic solvents. The specific steps include heating in the buffer and treating the starch solution with debranching enzymes, followed by shear homogenization, and adjusting electrospinning parameters such as voltage, flow rate and rotation speed to form nanofibers.

Benefits of technology

Bead-free, uniformly distributed starch nanofibers with an average diameter of 121-158nm are produced, which improves safety and adsorption performance and is suitable for food, medicine and cosmetics fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007628345000001
    Figure 0007628345000001
  • Figure 0007628345000002
    Figure 0007628345000002
  • Figure 0007628345000003
    Figure 0007628345000003
Patent Text Reader

Abstract

The present invention discloses a method for producing starch nanofibers by electrospinning. The method uses a debranched high-amylose solution as a starting material, which is shear-homogenized to form a spinning solution, followed by electrospinning to produce starch nanofibers. The process is simple and uses water as the only solvent, eliminating the need for organic solvents, making it green and environmentally friendly. The starch nanofibers produced have a perfect, bead-free fiber morphology and a uniform fiber diameter distribution, with an average fiber diameter of 121-158 nm. These nanofibers can be used as adsorbents, delivery carriers, and tissue stents in fields such as food, medicine, and cosmetics.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention belongs to the technical field of nanomaterial production, and relates to a method for producing starch nanofibers by electrospinning. [Background technology]

[0002] Starch nanofibers produced by electrospinning have characteristics such as high porosity, very high specific surface area, high biocompatibility, and biodegradability, and have great potential for application in medical fields such as drug delivery, wound dressing, and tissue engineering. Research on the application of natural starch to electrospinning began in 2012, when American scientist Ziegler et al. reported the production of starch fibers by "wet" electrospinning using dimethyl sulfoxide as the solvent and ethanol as the precipitant in the coagulation bath (Kong & Ziegler, Biomacromolecules, 2012, 13(8): 2247-2253). After that, domestic and foreign scholars respectively studied the spinning parameters (Kong & Ziegler, Carbohydrate Polymers, 2013, 92(2): 1416-1422), drum-oriented collection (Wang et al., Food hydrocolloids, 2019, 90: 113-117) and the composite of cellulose nanocrystals (Wang et al., Food Hydrocolloids, 2019, 90: 90-98), but it has defects such as a large amount of organic solvent used, a long drying time (> 6h), and a starch fiber diameter of micron size. Starch nanofibers (~ 146nm) can be obtained by thermal gelatinization of high amylose and composite electrospinning of fatty acid salt and pullulan, but there are still problems such as a long drying time (Wang & Ziegler, International Journal of Biological Macromolecules, 2019, 133: 1168-1174). Lancuski et al. were the first to report that starch nanofibers with diameters of 80-300 nm could be obtained by "dry" electrospinning using formic acid as a solvent. However, the use of formic acid caused methyl esterification of starch molecules and degradation of their molecular weight, and the time it took for formic acid to dissolve starch was too long (>24 h) (Lancuski et al., Biomacromolecules, 2015, 16(8):2529-2536).Currently, the processes for producing starch fibers by "wet" and "dry" electrospinning both require dissolving starch in a number of organic solvents (dimethyl sulfoxide and formic acid), which pose safety hazards and limit their application in the fields of food, medicine and cosmetics. Summary of the Invention [Problem to be solved by the invention]

[0003] An object of the present invention is to provide a method for producing starch nanofibers by electrospinning, which is a simple process and does not require the use of organic solvents. [Means for solving the problem]

[0004] The technical solutions to achieve the objectives of the present invention are as follows: In the method of producing starch nanofibers by electrospinning, shear homogenization increases the degree of intermolecular bonding in the debranched high amylose solution, improving the spinnability of starch nanofibers; Specifically, a 0.2-0.3 g / mL debranched high amylose solution is shear-homogenized at 10,000-20,000 rpm for 1-2 min to obtain an electrospinning solution, which is then placed in a 10-20 mL needle tubular syringe, and electrospun under the following electrospinning parameters: voltage 10-20 kV, spinning distance 10-20 cm, flow rate in the syringe 0.1-0.3 mL / h, and drum rotation speed 5-20 rpm to obtain starch nanofibers.

[0005] Preferably, the electrospinning time is 2 to 4 hours.

[0006] Preferably, the debranched high amylose solution comprises: (1) A step of dispersing high amylose at 0.2-0.3 g / mL in a buffer solution of pH 4.5-6.0, heating in a boiling water bath for 1-2 h, placing in a high-pressure sterilizer and treating at 121-142 °C for 20-60 min to obtain a sufficiently gelatinized high amylose solution; (2) placing the high amylose solution in a water bath at 50-65°C, adding 20-40 U / g of debranching enzyme, hydrolyzing for 12-24 hours, and then placing in a high-pressure sterilizer and treating at 121-142°C for 20-60 minutes to obtain a debranched high amylose solution;

[0007] Preferably, in step (1), the high amylose is high amylose corn starch or high amylose rice starch, the amylose content is 65-80%, and the buffer solution is a phosphate, acetate or citrate buffer solution.

[0008] Preferably, in step (2), the debranching enzyme is pullulanase or isoamylase, and the molecular weight of the debranched high amylose solution is 3 to 5 × 10 5 g / mol. Effect of the Invention

[0009] In the present invention, the debranched high amylose solution with high dispersibility and water soluble is used as the raw material, and the degree of intermolecular bonding in the debranched high amylose solution is increased by shear homogenization, and the spinnability of starch nanofibers is greatly improved without using organic solvents. The starch nanofibers produced by the method of the present invention have a perfect fiber morphology without beads, a uniform fiber diameter distribution, and an average fiber diameter of 121-158 nm, and are highly safe and can be used as adsorbents, transport carriers, and tissue stents in related fields such as food, medicine, and cosmetics. [Brief description of the drawings]

[0010] [Figure 1] 1 is a scanning electron microscope image of a debranched high amylose solution produced by the electrospinning method in Comparative Example 1. [Diagram 2]1 is a scanning electron microscope image of a debranched high amylose solution produced by the electrospinning method in Comparative Example 4. [Diagram 3] 1 is a scanning electron microscope image of a debranched high amylose solution produced by electrospinning in Comparative Example 6. [Figure 4] 1 is a scanning electron microscope image of starch nanofibers produced by the electrospinning method of Example 1. [Diagram 5] FIG. 2 is a fiber diameter distribution diagram of starch nanofibers produced by the electrospinning method of Example 1. [Figure 6] 1 is a scanning electron microscope image of starch nanofibers produced by the electrospinning method of Example 2. [Figure 7] FIG. 1 is a fiber diameter distribution diagram of starch nanofibers produced by the electrospinning method of Example 2. [Figure 8] 1 is a scanning electron microscope image of starch nanofibers produced by the electrospinning method of Example 3. [Figure 9] FIG. 1 is a fiber diameter distribution diagram of starch nanofibers produced by the electrospinning method of Example 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] In order to better understand the present invention, the present invention is further described below in combination with examples and drawings, but the scope of protection claimed in the present invention is not limited to the scope described in the examples.

[0012] The relevant test methods in the examples are described as follows: 1) Observation of samples using a scanning electron microscope The sample was fixed to a metal mounting stage with conductive adhesive and vacuum gold-plated for 90 s. The morphology of the sample was then observed with a scanning electron microscope (S-4800II, Hitachi, Japan) at 20,000x magnification and photographed. 2) Sample diameter analysis Analyze the above acquired scanning electron microscope images of the samples with ImageJ software, take 5-10 images for each sample, and take 50-100 points in each image to obtain the diameter data and then calculate the average diameter.

[0013] Comparative Example 1 (1) In the step of fully gelatinizing the high amylose corn starch, the high amylose corn starch (with an amylose content of 70%) is dispersed in a phosphate buffer solution of pH 5.0 at a mass concentration of 0.25 g / mL, heated in a boiling water bath for 1 h, and then placed in a high-pressure sterilizer and treated at 142°C for 20 min to obtain a fully gelatinized high amylose corn starch solution.

[0014] In step (2) of debranching enzymatic hydrolysis, the high amylose corn starch solution obtained in step (1) was placed in a water bath at 55°C, 40 U / g of isoamylase was added, and enzymatic hydrolysis was carried out for 24 hours. The solution was then placed in a high-pressure sterilizer at 121°C for 20 minutes to obtain a debranched high amylose corn starch solution (molecular weight of 3×10 5 g / mol).

[0015] In step (3) of producing starch nanofibers by electrospinning, the debranched high amylose corn starch solution obtained in step (2) is directly used as an electrospinning solution, which is placed in a 10 mL needle tubular syringe and equipped with a 20 G spinning needle. After electrospinning for 4 hours under the conditions of electrospinning voltage 15 kV, spinning distance 15 cm, flow rate in the syringe 0.1 mL / h, and drum rotation speed 5 rpm, a spun sample is obtained.

[0016] When the test was carried out, the scanning electron microscope images of the debranched high amylose solution samples obtained by electrospinning showed no fibrous structure, and the starch nanogranules were highly aggregated, as shown in Figure 1, indicating that the degree of intermolecular bonding in the debranched high amylose solution that had not been subjected to shear homogenization was insufficient and it was not spinnable.

[0017] Comparative Example 2 In step (1) of fully gelatinizing the high amylose corn starch, the high amylose corn starch (with an amylose content of 70%) is dispersed in a phosphate buffer solution of pH 5.0 at a mass concentration of 0.35 g / mL, heated in a boiling water bath for 1 h, and then placed in a high-pressure sterilizer and treated at 142°C for 20 min to obtain a fully gelatinized high amylose corn starch solution.

[0018] In step (2) of debranching enzymatic hydrolysis, the high amylose corn starch solution obtained in step (1) was placed in a water bath at 55°C, 40 U / g of isoamylase was added, and enzymatic hydrolysis was carried out for 24 hours. The solution was then placed in a high-pressure sterilizer at 121°C for 20 minutes to obtain a debranched high amylose corn starch solution (molecular weight of 3×10 5 g / mol).

[0019] In step (3) of producing starch nanofibers by electrospinning, the debranched high amylose corn starch solution obtained in step (2) is shear homogenized at 10,000 rpm for 1 minute to obtain an electrospinning solution, which is then placed in a 10 mL needle tubular syringe and equipped with a 20 G spinning needle. After electrospinning for 4 hours under the conditions of electrospinning voltage 15 kV, spinning distance 15 cm, flow rate in the syringe 0.1 mL / h, and drum rotation speed 5 rpm, a spun sample is obtained.

[0020] In the tests, it was found that a 0.35 g / mL debranched high amylose maize starch solution could not be used for electrospinning to obtain a spun sample, which may be because the concentration of the spinning solution was too high, making the solution too viscous and inhibiting the progress of electrospinning.

[0021] Comparative Example 3 In step (1) of fully gelatinizing the high amylose corn starch, the high amylose corn starch (with an amylose content of 70%) is dispersed in a phosphate buffer solution of pH 5.0 at a mass concentration of 0.15 g / mL, heated in a boiling water bath for 1 h, and then placed in a high-pressure sterilizer and treated at 142°C for 20 min to obtain a fully gelatinized high amylose corn starch solution.

[0022] In step (2) of debranching enzymatic hydrolysis, the high amylose corn starch solution obtained in step (1) was placed in a water bath at 55°C, 40 U / g of isoamylase was added, and enzymatic hydrolysis was carried out for 24 hours. The solution was then placed in a high-pressure sterilizer at 121°C for 20 minutes to obtain a debranched high amylose corn starch solution (molecular weight of 3×10 5 g / mol).

[0023] In step (3) of producing starch nanofibers by electrospinning, the debranched high amylose corn starch solution obtained in step (2) is shear homogenized at 10,000 rpm for 1 minute to obtain an electrospinning solution, which is then placed in a 10 mL needle tubular syringe and equipped with a 20 G spinning needle. After electrospinning for 4 hours under the conditions of electrospinning voltage 15 kV, spinning distance 15 cm, flow rate in the syringe 0.1 mL / h, and drum rotation speed 5 rpm, a spun sample is obtained.

[0024] Tests showed that a 0.15 g / mL debranched high amylose maize starch solution could not produce a fiber sample by electrospinning, possibly because the concentration of the spinning solution was too low, resulting in electrostatic spraying.

[0025] Comparative Example 4 In step (1) of fully gelatinizing the high amylose corn starch, the high amylose corn starch (containing 70% amylose) is dispersed in a phosphate buffer solution of pH 5.0 at a mass concentration of 0.25 g / mL, heated in a boiling water bath for 1 h, and then placed in a high-pressure sterilizer and treated at 142°C for 20 min to obtain a fully gelatinized high amylose corn starch solution.

[0026] In step (2) of debranching enzymatic hydrolysis, the high amylose corn starch solution obtained in step (1) was placed in a water bath at 55°C, 40 U / g of isoamylase was added, and enzymatic hydrolysis was carried out for 24 hours. The solution was then placed in a high-pressure sterilizer at 121°C for 20 minutes to obtain a debranched high amylose corn starch solution (molecular weight of 3×10 5 g / mol).

[0027] In step (3) of producing starch nanofibers by electrospinning, the debranched high amylose corn starch solution obtained in step (2) is shear homogenized at 5000 rpm for 1 minute to obtain an electrospinning solution, which is then placed in a 10 mL needle tubular syringe and equipped with a 20 G spinning needle. After electrospinning for 4 hours under the conditions of electrospinning voltage 15 kV, spinning distance 15 cm, flow rate in the syringe 0.1 mL / h, and drum rotation speed 5 rpm, a spun sample is obtained.

[0028] In the test, the scanning electron microscope images of the electrospun debranched high amylose solution samples showed a composite state of nanofibers and their “beads”, as shown in Figure 2. It was shown that shear homogenization can increase the degree of intermolecular bonding in the spinning solution and enhance its spinning effect, but if the rotation speed for shear homogenization is too low, perfect (without “beads”) starch nanofibers still cannot be obtained.

[0029] Comparative Example 5 In step (1) of fully gelatinizing the high amylose corn starch, the high amylose corn starch (containing 70% amylose) is dispersed in a phosphate buffer solution of pH 5.0 at a mass concentration of 0.25 g / mL, heated in a boiling water bath for 1 h, and then placed in a high-pressure sterilizer and treated at 142°C for 20 min to obtain a fully gelatinized high amylose corn starch solution.

[0030] In step (2) of debranching enzymatic hydrolysis, the high amylose corn starch solution obtained in step (1) was placed in a water bath at 55°C, 40 U / g of isoamylase was added, and enzymatic hydrolysis was carried out for 24 hours. The solution was then placed in a high-pressure sterilizer at 121°C for 20 minutes to obtain a debranched high amylose corn starch solution (molecular weight of 3×10 5 g / mol).

[0031] In step (3) of producing starch nanofibers by electrospinning, the debranched high amylose corn starch solution obtained in step (2) is shear homogenized at 25,000 rpm for 1 minute to obtain an electrospinning solution, which is then placed in a 10 mL needle tubular syringe and equipped with a 20 G spinning needle. After electrospinning for 4 hours under the conditions of electrospinning voltage 15 kV, spinning distance 15 cm, flow rate in the syringe 0.1 mL / h, and drum rotation speed 5 rpm, a spun sample is obtained.

[0032] In tests, it was found that spinning samples could not be obtained from debranched high amylose corn starch solutions that had been subjected to shear homogenization treatment at too high a rotation speed. Although shear homogenization can increase the degree of intermolecular bonding in the spinning solution, if the rotation speed for shear homogenization is too high, the viscosity of the spinning solution also increases significantly at the same time, which inhibits the progress of electrospinning.

[0033] Comparative Example 6 In step (1) of fully gelatinizing the high amylose corn starch, the high amylose corn starch (containing 70% amylose) is dispersed in a phosphate buffer solution of pH 5.0 at a mass concentration of 0.25 g / mL, heated in a boiling water bath for 1 h, and then placed in a high-pressure sterilizer and treated at 142°C for 20 min to obtain a fully gelatinized high amylose corn starch solution.

[0034] In step (2) of debranching enzymatic hydrolysis, the high amylose corn starch solution obtained in step (1) was placed in a water bath at 55°C, 40 U / g of isoamylase was added, and enzymatic hydrolysis was carried out for 24 hours. The solution was then placed in a high-pressure sterilizer at 121°C for 20 minutes to obtain a debranched high amylose corn starch solution (molecular weight of 3×10 5 g / mol).

[0035] In step (3) of producing starch nanofibers by electrospinning, the debranched high amylose corn starch solution obtained in step (2) is shear homogenized at 10,000 rpm for 0.5 min to obtain an electrospinning solution, which is then placed in a 10 mL needle tubular syringe and equipped with a 20 G spinning needle. After electrospinning for 4 h under the conditions of electrospinning voltage 15 kV, spinning distance 15 cm, flow rate in the syringe 0.1 mL / h, and drum rotation speed 5 rpm, a spun sample is obtained.

[0036] In the test, the scanning electron microscope image of the electrospun debranched high amylose solution sample showed a composite state of nanofibers and their "beads", as shown in Figure 3, which is similar to Figure 2. The effects of too short shear homogenization time and too low shear homogenization rotation speed on starch electrospinning were similar, which indicated that shear homogenization can increase the degree of intermolecular bonding in the spinning solution and enhance its spinning effect, but neither too short shear homogenization time nor too low shear homogenization rotation speed can obtain perfect (without "beads") starch nanofibers.

[0037] Comparative Example 7 In step (1) of fully gelatinizing the high amylose corn starch, the high amylose corn starch (containing 70% amylose) is dispersed in a phosphate buffer solution of pH 5.0 at a mass concentration of 0.25 g / mL, heated in a boiling water bath for 1 h, and then placed in a high-pressure sterilizer and treated at 142°C for 20 min to obtain a fully gelatinized high amylose corn starch solution.

[0038] In step (2) of debranching enzymatic hydrolysis, the high amylose corn starch solution obtained in step (1) was placed in a water bath at 55°C, 40 U / g of isoamylase was added, and enzymatic hydrolysis was carried out for 24 hours. The solution was then placed in a high-pressure sterilizer at 121°C for 20 minutes to obtain a debranched high amylose corn starch solution (molecular weight of 3×10 5 g / mol).

[0039] In step (3) of producing starch nanofibers by electrospinning, the debranched high amylose corn starch solution obtained in step (2) is shear homogenized at 10,000 rpm for 2.5 min to obtain an electrospinning solution, which is then placed in a 10 mL needle tubular syringe and equipped with a 20 G spinning needle. After electrospinning for 4 h under the conditions of electrospinning voltage 15 kV, spinning distance 15 cm, flow rate in the syringe 0.1 mL / h, and drum rotation speed 5 rpm, a spun sample is obtained.

[0040] In the test, it was found that it was not possible to obtain a spinning sample from a debranched high amylose corn starch solution that had been subjected to a shear homogenization treatment at too high a rotation speed. Although shear homogenization can increase the degree of intermolecular bonding in the spinning solution, if the shear homogenization is performed for too long, the viscosity of the spinning solution also increases significantly at the same time, which inhibits the progress of electrospinning.

[0041] Example 1 The method for producing starch nanofibers by electrospinning is as follows: (1) thoroughly gelatinizing the high amylose corn starch by dispersing high amylose corn starch (70% amylose content) in a phosphate buffer solution of pH 5.0 at a mass concentration of 0.25 g / mL, heating in a boiling water bath for 1 h, and then placing in a high-pressure sterilizer for 20 min at 142 ° C to obtain a fully gelatinized high amylose corn starch solution; The high amylose corn starch solution obtained in step (1) was placed in a water bath at 55°C, 40 U / g of isoamylase was added, and the solution was enzymatically hydrolyzed for 24 hours. The solution was then placed in a high-pressure sterilizer at 121°C for 20 minutes to obtain a debranched high amylose corn starch solution (molecular weight of 3×10 5 (2) carrying out a debranching enzyme digestion to obtain a product of 100 g / mol; and (3) producing starch nanofibers by electrospinning, in which the debranched high amylose corn starch solution obtained in step (2) is shear-homogenized at 10,000 rpm for 1 minute to obtain an electrospinning solution, which is then placed in a 10 mL needle tubular syringe, and a 20 G spinning needle is attached. After electrospinning for 4 hours under the conditions of an electrospinning voltage of 15 kV, a spinning distance of 15 cm, a flow rate in the syringe of 0.1 mL / h, and a drum rotation speed of 5 rpm, starch nanofibers are obtained.

[0042] Testing showed that the spun samples had perfect, bead-free fiber morphology and uniform fiber diameter distribution (Figure 4), with an average fiber diameter of 121 nm (Figure 5).Compared with Comparative Example 1 (Figure 1), the shear homogenization enhanced the intermolecular bonding degree in the debranched high amylose solution, which greatly improved the spinnability of starch nanofibers by electrospinning.

[0043] Example 2 The method for producing starch nanofibers by electrospinning is as follows: High amylose rice starch (amylose content 65%) is dispersed in a phosphate buffer solution of pH 4.5 at a mass concentration of 0.3 g / mL, heated in a boiling water bath for 2 h, and then placed in a high-pressure sterilizer for 60 min at 121 °C to obtain a fully gelatinized high amylose rice starch solution. When high amylose rice starch is fully gelatinized (1), The high amylose rice starch solution obtained in step (1) was placed in a water bath at 60°C, 30 U / g of isoamylase was added, and the solution was enzymatically hydrolyzed for 18 hours. The solution was then placed in a high-pressure sterilizer at 142°C for 30 min to obtain a high amylose rice starch debranched solution (molecular weight of 3.9 × 10 5 (2) carrying out a debranching enzyme digestion to obtain a product of 100 g / mol; and (3) producing starch nanofibers by electrospinning, in which the high amylose rice starch debranched solution obtained in step (2) is shear homogenized at 15,000 rpm for 2 minutes to obtain an electrospinning solution, which is then placed in a 20 mL needle tubular syringe, and an 18 G spinning needle is attached. After electrospinning for 2 hours under the conditions of an electrospinning voltage of 20 kV, a spinning distance of 10 cm, a flow rate in the syringe of 0.3 mL / h, and a drum rotation speed of 20 rpm, a spun sample can be obtained.

[0044] When tested, the resulting spun samples had perfect, bead-free fiber morphology and a uniform fiber diameter distribution (Figure 6), with an average fiber diameter of 131 nm (Figure 7).

[0045] Example 3 The method for producing starch nanofibers by electrospinning is as follows: (1) A step of thoroughly gelatinizing the high amylose corn starch by dispersing the high amylose corn starch (having an amylose content of 80%) in a phosphate buffer solution of pH 6.0 at a mass concentration of 0.2 g / mL, heating in a boiling water bath for 2 h, and then placing in a high-pressure sterilizer for 60 min at 135°C to obtain a fully gelatinized high amylose solution; The high amylose corn starch solution obtained in step (1) was placed in a water bath at 55°C, 40 U / g of isoamylase was added, and the solution was enzymatically hydrolyzed for 24 hours. The solution was then placed in a high-pressure sterilizer and treated at 141°C for 20 minutes to obtain a debranched high amylose corn starch solution (molecular weight of 5×10 5 (2) carrying out a debranching enzyme digestion to obtain a product of 100 g / mol; and (3) producing starch nanofibers by electrospinning, in which the debranched high amylose corn starch solution obtained in step (2) is shear-homogenized at 20,000 rpm for 2 minutes to obtain an electrospinning solution, which is then placed in a 15 mL needle tubular syringe, and a 23 G spinning needle is attached. After electrospinning for 3 hours under the conditions of an electrospinning voltage of 10 kV, a spinning distance of 20 cm, a flow rate in the syringe of 0.3 mL / h, and a drum rotation speed of 10 rpm, a spun sample can be obtained.

[0046] When tested, the resulting spun samples had perfect, bead-free fiber morphology and a uniform fiber diameter distribution (Figure 8), with an average fiber diameter of 158 nm (Figure 9).

[0047] The present invention uses debranched high amylose solution as raw material. In the preparation process of debranched high amylose solution, first, high amylose is treated at high temperature in boiling water bath and high pressure sterilization pot to fully gelatinize, completely opening the double helical structure inside starch, and then debranched enzymatically to obtain debranched starch solution, improving its water solubility. However, if the enzymatic decomposition process is too long, part of amylose will recrystallize, so high temperature treatment is performed in high pressure sterilization pot to open part of the helical structure of recrystallized amylose, to obtain debranched high amylose solution with high dispersibility. High temperature treatment in high pressure sterilization pot and debranched enzymatic decomposition greatly improve the enzymatic decomposition efficiency and water solubility of high amylose, and the use of organic solvents such as dimethyl sulfoxide and formic acid is avoided. In addition, shear homogenization treatment increases the degree of intermolecular bonding in the debranched high amylose solution, and the spinnability of starch nanofibers by electrospinning method is greatly improved.

[0048] (Additional Note) (Appendix 1) Specifically, a 0.2-0.3 g / mL debranched high amylose solution is shear-homogenized at 10,000-20,000 rpm for 1-2 min to obtain an electrospinning solution, which is then placed in a 10-20 mL needle tubular syringe, and electrospun under the following electrospinning parameters: voltage 10-20 kV, spinning distance 10-20 cm, flow rate in the syringe 0.1-0.3 mL / h, and drum rotation speed 5-20 rpm to obtain starch nanofibers. A method for producing starch nanofibers by electrospinning, comprising:

[0049] (Appendix 2) The electrospinning time is 2 to 4 hours. The method according to claim 1,

[0050] (Appendix 3) The debranched high amylose solution comprises: (1) A step of dispersing high amylose at 0.2-0.3 g / mL in a buffer solution of pH 4.5-6.0, heating in a boiling water bath for 1-2 h, placing in a high-pressure sterilizer and treating at 121-142 °C for 20-60 min to obtain a sufficiently gelatinized high amylose solution; (2) placing the high amylose solution in a water bath at 50-65°C, adding 20-40U / g of debranching enzyme, enzymatically hydrolyzing for 12-24 hours, and then placing it in a high-pressure sterilizer and treating at 121-142°C for 20-60 minutes to obtain a debranched high amylose solution; The method according to claim 1,

[0051] (Appendix 4) In step (1), the high amylose is high amylose corn starch or high amylose rice starch. The method according to claim 3,

[0052] (Appendix 5) In step (1), the content of the high amylose amylose is 65-80%; The method according to claim 3,

[0053] (Appendix 6) In step (1), the buffer solution is a phosphate, acetate or citrate buffer solution; The method according to claim 3,

[0054] (Appendix 7) In step (2), the debranching enzyme is pullulanase or isoamylase. The method according to claim 3,

[0055] (Appendix 8) In step (2), the molecular weight of the debranched high amylose solution is 3 to 5 × 10 5 g / mol, The method according to claim 3,

Claims

1. A 0.2-0.3 g / mL debranched high amylose solution is shear-homogenized at 10,000-20,000 rpm for 1-2 min to obtain an electrospinning solution, which is then placed in a 10-20 mL needle tubular syringe, and electrospun under the following electrospinning parameters: voltage 10-20 kV, spinning distance 10-20 cm, flow rate in the syringe 0.1-0.3 mL / h, and drum rotation speed 5-20 rpm to obtain starch nanofibers. A method for producing starch nanofibers by electrospinning, comprising:

2. The electrospinning time is 2 to 4 h.

2. The method of claim 1 .

3. The debranched high amylose solution comprises: (1) dispersing high amylose in a buffer solution of pH 4.5-6.0 to a concentration of 0.2-0.3 g / mL, heating in a boiling water bath for 1-2 h, placing in a high-pressure sterilizer and treating at 121-142° C. for 20-60 min to obtain a sufficiently gelatinized high amylose solution; (2) placing the high amylose solution in a water bath at 50-65°C, adding 20-40U / g of debranching enzyme, enzymatically hydrolyzing for 12-24h, then placing in a high-pressure sterilizer and treating at 121-142°C for 20-60min to obtain a debranched high amylose solution; 2. The method of claim 1 .

4. In step (1), the high amylose is high amylose corn starch or high amylose rice starch.

4. The method according to claim 3 .

5. In step (1), the amylose content in the high amylose is 65-80%.

4. The method according to claim 3 .

6. In step (1), the buffer solution is a phosphate, acetate or citrate buffer solution.

4. The method according to claim 3 .

7. In step (2), the debranching enzyme is pullulanase or isoamylase.

4. The method according to claim 3 .

8. In step (2), the molecular weight of the debranched high amylose solution is 3 to 5×10 5 g / mol, 4. The method according to claim 3 .

Citation Information

Patent Citations

  • Preparation method of high amylose

    CN106498003A

  • Colon-targeted ferulic acid controlled-release carrier and preparation method thereof

    CN112336683A

  • Starch-based drug-loaded nanofiber membrane as well as preparation method and application thereof

    CN113509452A

  • Electric spinning for making starch filament of flexible structure

    JP2002201531A

  • Methods and compositions relating to starch fibers

    US20150045454A1